2015
DOI: 10.1007/s11547-015-0570-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging (MRI) of the lumbar spine with dedicated G-scan machine in the upright position: a retrospective study and our experience in 10 years with 4305 patients

Abstract: The G-scan is useful to assess instability of the lumbar spine detecting hidden modifications of protrusions and/or herniated discs already present in the supine position. It is also helpful in assessing the presence or modification of spondylolisthesis and lumbar canal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Splendiani et al [1] found in a large sample of patients significant differences in the evaluation of degenerative aspects analyzed with dynamic MR in the transition from standing to supine position; in particular, the appearance of disc protrusions was significantly detected in 11 % of the cases, as well as the increase or appearance of spinal canal stenosis in 9.2 % of the cases; these data are in agreement with other previous published studies [9,24,25] performed with open dynamic MR magnets.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Splendiani et al [1] found in a large sample of patients significant differences in the evaluation of degenerative aspects analyzed with dynamic MR in the transition from standing to supine position; in particular, the appearance of disc protrusions was significantly detected in 11 % of the cases, as well as the increase or appearance of spinal canal stenosis in 9.2 % of the cases; these data are in agreement with other previous published studies [9,24,25] performed with open dynamic MR magnets.…”
Section: Discussionsupporting
confidence: 87%
“…In many cases, dynamic MR has proven [1,9,13,24,25] to reveal disc-radicular conflicts not depictable on conventional MR studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations